Relationship between mitral annular calcification and first degree atrioventricular block in elderly (Annals of Medical Research, 2023)
Aim: In this study, we aimed to reveal the relationship between these two degenerative processes, mitral annular calcification, and first-degree AV block.Materials and Methods: The data of 2,347 patients over the age of 65 who were examined in the cardiology outpatient clinic. A total of 389 patients with echocardiography results and 12-lead ECGs obtained at the same visit were included in their electronic records. The patient population was divided into two groups as those with or without first-degree AV block, and those with or without mitral annular calcification.Results: Considering the relationship between mitral annular calcification and first-degree AV block, first-degree AV block was observed more frequently in patients with mitral annular calcification, and this was statistically significant. [(Odds ratio: 6.881; 3.107 – 15.236 (95% CI), p
Keywords: Mitral calcification; Conduction disturbance; AV block